2022
DOI: 10.1108/bij-08-2021-0497
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the revival strategies of Indian MSMEs to mitigate the effects of COVID-19 outbreak

Abstract: Purpose Micro, small and medium enterprise (MSME) is the kingpin of Indian economy. It contributes to 48% of India's exports and provides employment to 110 million people. As a result, it is critical to evaluate the obstacles, expose them and find a way to overcome the crisis due to the pandemic. The study aims to analyse the impact of financial and non-financial measures for the revival of MSME and its impact on firm sustainability and future opportunity as perceived by MSME owners/heads during the COVID-19 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 59 publications
(172 reference statements)
1
26
0
Order By: Relevance
“…Entrepreneurs' adoption of digital technology has accelerated, particularly during the pandemic. For micro-enterprises to cultivate, digital literacy is required, skills must be improved, e-commerce must be widely accepted within the sector, and marketing strategies must be modified (Effendy, 2018;Singh et al 2022). During the COVID-19 pandemic, digital marketing positively affected firm performance in terms of increased sales, improved customer relationships, and increased productivity and creativity (Syaifullah et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Entrepreneurs' adoption of digital technology has accelerated, particularly during the pandemic. For micro-enterprises to cultivate, digital literacy is required, skills must be improved, e-commerce must be widely accepted within the sector, and marketing strategies must be modified (Effendy, 2018;Singh et al 2022). During the COVID-19 pandemic, digital marketing positively affected firm performance in terms of increased sales, improved customer relationships, and increased productivity and creativity (Syaifullah et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In this investigation, first, primary data were collected from Indian citizens using an online survey question developed collected from May 2021 to July 2021. Citizens were requested to engage in the research process via email, and the questionnaire was posted on several social media sites such as LinkedIn, Research Gate, and Facebook, with potential respondents being directed to the website to complete the survey (Paliwal et al, 2022;Singh et al, 2022). There were three sections to the survey questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…SMEs found in developing countries have also fallen prey of the negative effects of COVID-19. For instance, MSMEs are considered to be kingpin of the Indian economy contributing to 48% of India's export and employing around 110 million people (Singh et al, 2022). In this context, Dun & Bradstreet (2021) conducted a survey to assess the impact COVID-19 on small businesses in India and the results revealed that 82% of the respondents were negatively impacted by the pandemic with a fall in turnover and lack of inputs, lesser access to credit facilities and a massive reduction in demand for their products.…”
Section: Literature Review 21 Impact Of Covid-19 On Smes In Developed...mentioning
confidence: 99%
“…SMEs found in developing countries have also fallen prey of the negative effects of COVID-19. For instance, MSMEs are considered to be kingpin of the Indian economy contributing to 48% of India's export and employing around 110 million people (Singh et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%